Distribution of the population of tongkat Ali (Eurycoma Spp.) in Malaysia based on data taken from herbarium records - Nordin, Mohd Shukor (2014)
Eurycoma spp., also known locally as Tongkat Ali is considered the most popular medicinal plant in Malaysia. The tremendous attention put to it by the public for its medicinal properties has led to its non-selective harvesting at a very alarming rate. Concerted efforts by a number of institutions in the country have been initiated to manage, conserve and recommend a sustainable way of utilizing them. A program to study the genetic diversity of Eurycoma species population, its distribution throughout country and to conserve its genetic resources in situ as well as ex situ has been carried out. As the first step, a preliminary study was conducted to get an idea the kinds of species occurring in the country, its general distribution, preferred habitat, and to look for various observable variations between and within species. Data used in this study was obtained from sixty eight herbarium records, dated back as far as 1930, which were kept in herbarium units located at the various local universities and research institutions within Malaysia. The results indicate that there are two species of Eurycoma found in Malaysia namely E. longifolia and E. apiculata with very little difference to differentiate between them except that apiculata has slightly bigger leaf size. Eurycoma spp. is called by six different local names. Specimens of Eurycoma longifolia and E. apiculata kept in the herbariums were mainly collected from zone 1, 2 and 3. The climatical descriptions of each zone are presented thus giving some indications of its preferred habitat and the locations where the diversity of the species are at the highest. The majority of the apiculata specimens were collected from hilly areas deep in the forest thus is in agreement with the previous findings which stated that apiculata is a mountain species. Flora MapR software was used to predict the areas of possible adaptation of E. Longifolia in Malaysia and the map showing the probability distribution is presented. The map can assist in future germplasm collection and conservation.